ASPHALTEN-RESISTANCE AND PARAFFIN SEDIMENTS - Fokeeva, Liya; Zainyllina, Vilena (Revista Inclusiones, 2019)
His article discusses the implementation of a comprehensive program of technical reequipment of oil and gas production. Methods of combating the formation of ASPO in wells, the intensive introduction into the production of new equipment and technology, automation and automated production management systems are analyzed and reviewed. Based on the analysis performed, the use of acceptable methods to reduce the formation of ARPD was justified.